Effective treatment with mepolizumab in a patient with severe eosinophilic granulomatosis with polyangiitis complicated with small intestine perforation. (2023) - Sato, Mari; Yatomi, Masakiyo; Wakamatsu, Ikuo; Uno, Shogo; Hanazato, Chiharu; Masuda, Tomomi; Yamaguchi, Koichi; Aoki-Saito, Haruka; Kasahara, Norimitsu; Miura, Yosuke; Tsurumaki, Hiroaki; Hara, Kenichiro; et al.
Abstract: Eosinophilic granulomatosis with polyangiitis (EGPA) is systemic vasculitis caused by eosinophilia affecting small to medium-sized blood vessels, which damages the organs. Antineutrophil cytoplasmic antibody-associated vasculitis EGPA treatment guidelines added anti-interleukin-5 antibody mepolizumab to the standard treatment protocol for active-non-severe EGPA based on the MIRRA study. Nevertheless, the role of mepolizumab in treating patients with active severe EGPA has not been established. We treated a patient with EGPA complicated with small intestine perforation using steroid pulse intravenous, high-dose glucocorticoids, intravenous high-dose immunoglobulin therapy, and mepolizumab without immunosuppression agents; the patient went into remission, suggesting that mepolizumab is an effective therapeutic agent that could lead to remission in severe EGPA.